Anatomic Study and Clinical Significance of the Dorsal Meningovertebral Ligaments of the Thoracic Dura Mater. Issue 10 (15th May 2015) - Chen, Rongzi; Shi, Benchao; Zheng, Xuefeng; Zhou, Zhilai; Jin, Anmin; Ding, Zihai; LV, Hai; Zhang, Hui
Abstract : Study Design: A dissection-based study of 18 embalmed thoracic specimens. Objective: To investigate the properties and clinical significance of the dorsal meningovertebral ligaments of the thoracic dura mater. Summary of Background Data: Previously, we performed a comprehensive anatomic study on the dorsal meningovertebral ligaments in the lumbosacral and cervical regions, whereby we concluded that the ligaments were an anatomic factor leading to dural laceration and hemorrhage during flavectomy and laminectomy. Unfortunately, thus far, no systematic anatomic study has been undertaken to examine the dorsal meningovertebral ligaments of the thoracic dura mater. Methods: Eighteen adult embalmed cadavers were studied, and the morphology, orientation, attachment site, and distribution traits of the dorsal meningovertebal ligaments were observed. In addition, the length, width, or diameter and thickness of the ligaments were measured using a Vernier caliper. Two meningovertebal ligaments were removed for histological examination. Results: In the thoracic region, the dorsal meningovertebral ligaments anchored the dura mater to the lamina or ligamentum flavum. The meningovertebral ligaments displayed a relatively even distribution along the upper thoracic region (T1–T7) and a gradual increase in frequency in the lower thoracic region from T7 to T12. The meningovertebral ligaments protrude into the dura and correspondingly become an integral part of the dura. Some ligaments are accompanied by or are attached to blood vessels. Histological examination of the meningovertebral ligaments revealed fibrous connective tissue. Conclusion: The dorsal meningovertebral ligaments exist between the dural sac and ligamentum flavum or lamina in the thoracic spine. Based on their anatomic features, meningovertebral ligaments may be one potential cause for dural laceration and epidural hemorrhage. We propose that, during thoracic flavectomy and laminectomy, the meningovertebral ligaments should first be identified and properly handled, thereby minimizing the occurrence of relevant complications. Level of Evidence: N/A Abstract : Eighteen cadaveric thoracic specimens were obtained. The morphology and morphometry of the dorsal meningovertebral ligaments of the thoracic dura mater were described and analyzed. This study suggests that these ligaments may be the anatomical factor underlying dura laceration and epidural hemorrhage and should be identified and properly handled.